2006
DOI: 10.1177/10634266060140030301
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Strain Among Types of Caregivers Responsible for Children With Serious Emotional and Behavioral Disorders

Abstract: Parents and relative caregivers of children with severe emotional and behavioral disorders (EBD) often report high levels of strain associated with the care of that child.This study compares how parents and other relative caregivers, and different family caregiver groups, experience strain. Overall, we found that Medicaid caregivers ( n = 648) reported high levels of objective strain, whereas military caregivers ( n = 978) had high scores on the subjective internalized and externalized subscales of the Caregiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 36 publications
3
40
0
Order By: Relevance
“…Overall, this suggested that having a child with a HFASDs may indeed negatively influence parents' QOL. This finding is generally consistent with existing literature reflecting lower levels of physical health and mental health for parents of children with developmental disabilities, as well as with some initial reports for parents of children with ASDs (e.g., Benson, 2006;Hastings, 2003;Hastings et al, 2005;Murphy et al, 2007;Pakenham et al, 2005;Taylor-Richardson et al, 2006;Tomanik et al, 2004;Whitley et al, 2001). Compared to the control group, parents of children with HFASDs in this sample reported significantly higher levels of stress and significantly lower levels of adaptive coping and res ources.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, this suggested that having a child with a HFASDs may indeed negatively influence parents' QOL. This finding is generally consistent with existing literature reflecting lower levels of physical health and mental health for parents of children with developmental disabilities, as well as with some initial reports for parents of children with ASDs (e.g., Benson, 2006;Hastings, 2003;Hastings et al, 2005;Murphy et al, 2007;Pakenham et al, 2005;Taylor-Richardson et al, 2006;Tomanik et al, 2004;Whitley et al, 2001). Compared to the control group, parents of children with HFASDs in this sample reported significantly higher levels of stress and significantly lower levels of adaptive coping and res ources.…”
Section: Discussionsupporting
confidence: 90%
“…Researchers suggest that caregivers' health may be jeopardized owing to the strain of caring for a child with a disability (e.g., Chou, Lin, & Chang, 2007;Taylor-Richardson et al, 2006;Whitley, Kelley, & Sipe, 2001). Murphy, Christian, Caplin, and Young (2007) qualitatively examined the reports of 40 parents who provided long-term care for their children with severe disabilities.…”
Section: Physical Health Status Of Caregivers Of Children With Disabimentioning
confidence: 99%
“…Higher scores in each dimension reflect more strain. In a sample of caregivers receiving Medicaid (Taylor-Richardson, Heflinger & Brown, 2006), reliability alpha coefficients were .93 for the objective strain scale, .93 for the subjective internalized strain scale, and .78 for the objective externalized strain scale. Internal consistency alpha coefficients for the sample in the current sample were .91 for the objective strain scale, .83 for the subjective internalized strain scale and .75 for the subjective externalized strain scale.…”
Section: Methodsmentioning
confidence: 99%
“…Historically, the literature on caregiver strain has focused on caring for persons with dementia (Schulz & Martire, 2004), adult children with severe mental illness (Saunders, 2003), or children with developmental disabilities (Green, 2007). Research investigating the impact of child and adolescent emotional and behavioral difficulties on caregiver strain has also received considerable attention (Angold, et al, 1998; Sales, Greeno, Shear, & Anderson, 2004; Taylor-Richardson, et al, 2006). Parenting stress, another important parental outcome is the adverse impact of efforts to adapt to parenting tasks and roles.…”
mentioning
confidence: 99%
“…Youth are also at risk of cycling through multiple hospitalizations in a short period of time (Fontanella 2008). Caregivers of youth with EBD experience high levels of financial strain and emotional stress (Brannan and Heflinger 2001;Taylor-Richardson et al 2006). For youth with severe EBD, caregiver strain (e.g., the demands, responsibilities, difficulties, and negative consequences of caring for relatives with special needs) is particularly high (Angold et al 1998;Brannan et al 1997;Vaughan et al 2013).…”
Section: Introductionmentioning
confidence: 96%